A single‐center retrospective comparison of Duplex ultrasonography versus audible Doppler regarding anterolateral thigh perforator flap harvest and operative times. Issue 1 (24th June 2021) - Thomas, Benjamin; Haug, Valentin; Falkner, Florian; Arras, Christian; Nagel, Sarah S.; Boecker, Arne; Schmidt, Volker J.; Kneser, Ulrich; Bigdeli, Amir K.
Abstract: Introduction: We reported on the superiority of preoperative Duplex mapping ("Duplex") over audible Dopplers ("Doppler") in anterolateral thigh perforator (ALT) free flaps for upper extremity reconstruction. To corroborate our findings on a larger cohort, we conducted this present study focusing on surgical efficiency and patient safety. Methods: 150 consecutive ALT free flaps were divided into 65 cases of preoperative Duplex versus 85 Doppler controls. We first compared patient demographics, operative details, and defect and flap characteristics. We then assessed group differences in the number and course of perforators pursued intraoperatively, flap harvest and operative times, and donor‐site complications. Additionally, the impact of the training level of the primary microsurgeon was evaluated. Results: Cases and controls were comparable regarding age ( p = .48), sex ( p = .81), ASA class ( p = .48), and BMI ( p = .90). Duplex was associated with an increased likelihood of raising flaps on one single dominant perforator of purely septal course and significant reductions of flap harvest (68 ± 10 min, p < .0001) and operative times (74 ± 16 min, p < .0001), regardless of the experience of the primary microsurgeon. There were strong negative linear correlations between preoperative Duplex and both the flap harvest and operative times ( p < .0001). Additionally, while there was no effect on the emergency take‐back rate (OR = 1.3, p = .60), revisions were significantly less likely among duplexed patients (OR = 0.15, p = .04). Conclusions: Preoperative Duplex is associated with a significant reduction in ALT free flap harvest and overall operative times, as well as donor‐site revisions as opposed to Doppler planning, regardless of the training level of the primary microsurgeon.